PENGERTIAN ULUMUL QUR’AN, SEJARAH DAN PERKEMBANGAN STUDI ILMU AL QUR’AN - Ani Marlia; Dealfi Anggun Fratiwi; Sodikin; Nova Marisa; Indi Novita Sari; Adela Agustin; Yulia Arwiyah Nst (Kampus Akademik Publiser, 2024)
This study aims to discuss fundamentally the meaning of Ulumul Qur’an, the history and development of the study of Qur’anic science. This research method is qualitative by using descriptive method through theoretical analysis and literature study. The results of this study conclude that Ulumul Qur’an is a science that discusses the Qur’an as explained by AzZarqani, and explains the history of the scope and subject matter. This research has significance for the development of the Qur’anic Science discourse, considering that the discourse on the Ulumul Qur’an has a lot of lightening. The conclusion of this research is the study of Ulumul Qur’an has an important role in understanding the Qur’an systematically and comprehensively.